2022
DOI: 10.3390/ijms23126530
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of Switchgrass Laccases Involved in Lignin Biosynthesis and Heavy-Metal Responses

Abstract: Plant laccase genes belong to a multigene family, play key roles in lignin polymerization, and participate in the resistance of plants to biotic and abiotic stresses. Switchgrass is an important resource for forage and bioenergy production, yet information about the switchgrass laccase gene family is scarce. Using bioinformatic approaches, a genome-wide analysis of the laccase multigene family in switchgrass was carried out in this study. In total, 49 laccase genes (PvLac1 to PvLac49) were identified; these ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…The most abundant laccases were observed in Swetha (n = 56), followed by Zhongzhi13 (n = 48), Goenbaek (n = 45), Baizhima (n = 42), Yuzhi11 (n = 40), and Mishuozhima (n = 35). Similar laccases counts were observed in land plants Prunus persica (n = 48) [ 82 ], Panicum virgatum (n = 49) [ 83 ], and Solanum melongena (n = 42) [ 84 ]; a lower number of laccase genes was reported in A. thaliana (n = 17) [ 85 ].…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The most abundant laccases were observed in Swetha (n = 56), followed by Zhongzhi13 (n = 48), Goenbaek (n = 45), Baizhima (n = 42), Yuzhi11 (n = 40), and Mishuozhima (n = 35). Similar laccases counts were observed in land plants Prunus persica (n = 48) [ 82 ], Panicum virgatum (n = 49) [ 83 ], and Solanum melongena (n = 42) [ 84 ]; a lower number of laccase genes was reported in A. thaliana (n = 17) [ 85 ].…”
Section: Resultssupporting
confidence: 71%
“…In contrast, only a tandem duplication pattern was detected in Solanum melongena with 16 laccase genes [ 84 ]. In Panicum virgatum , both tandem and segmental duplications of laccase genes were found [ 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, our previous study revealed that the LTR motif ( cis -acting element involved in low-temperature responsiveness) was predicted to be located in the promoter regions of eight chilling-responsive CsLACs [ 18 ]. Moreover, low-temperature cis -elements were found in the promoters of 8 LACs from Brassica napus [ 29 ], 11 LACs from eggplant [ 17 ], 21 LACs from switchgrass [ 30 ], 12 LACs from tea plant [ 31 ], 45 LACs from wheat [ 32 ], and 16 LACs from peach [ 33 ]. Therefore, the above results indicate that low-temperature cis -elements are essential for the LACs to respond to cold stress.…”
Section: Discussionmentioning
confidence: 99%
“…Research into heavy metal tolerance is increasing as major cereal crops are experiencing significant yield loss due to irrigation containing zinc (Zn), ferrous iron (Fe), nickel (Ni), copper (Cu), cadmium (Cd), chromium (Cr), and lead (Pb) from industrial runoff (Mir et al, 2021;Riyazuddin et al, 2022;Skuza et al, 2022;Li et al, 2022b;Xu et al, 2023). Mounting evidence suggests cell wall thickening of both woody and herbaceous plants contributes a partial but significant exclusion barrier where heavy metals are sequestered via ion exchange and chelation with methylesterified pectins, phenolic acids, organic acids, and ROS (Krzeslowska, 2011;Parrotta et al, 2015;Berni et al, 2019;Gao et al, 2021;Sytar et al, 2021) (Table 1).…”
Section: Lac Activity Likely Contributes To Heavy Metal Ion Sequestra...mentioning
confidence: 99%